MORPHOLOGICAL FEATURES OF MUCOUS MEMBRANE OVER IMPACTED TEETH DEPENDENING ON CONDITIONS OF THEIR POSITION - P.I. Tkachenko; I.I. Starchenko; M.I. Dmytrenko; M.O. Cholovskyi (Український стоматологічний альманах, 2020)
Impacted teeth are rather common and complex dentofacial anomaly, which requires a balanced approach not only in differential diagnosis of its specific nosological form, but also in a choice of rational treatment methods. Taking into account the multi-factor nature of conditions formation for delay of teeth eruption, an approach to treatment should be directed towards guiding links of pathogenesis.